Mechanisms of microbe-mediated immune development in the context of antibiotics and asthma - Donald, Katherine; Finlay, B. Brett (Frontiers in Allergy, 2024)
The gut houses 70%–80% of the body's immune cells and represents the main point of contact between the immune system and the outside world. Immune maturation occurs largely after birth and is guided by the gut microbiota. In addition to the many human clinical studies that have identified relationships between gut microbiota composition and disease outcomes, experimental research has demonstrated a plethora of mechanisms by which specific microbes and microbial metabolites train the developing immune system. The healthy maturation of the gut microbiota has been well-characterized and discreet stages marked by changes in abundance of specific microbes have been identified. Building on Chapter 8, which discusses experimental models used to study the relationship between the gut microbiota and asthma, the present review aims to dive deeper into the specific microbes and metabolites that drive key processes in immune development. The implications of microbiota maturation patterns in the context of asthma and allergies, as well as the effects of antibiotics on microbe-immune crosstalk, will also be discussed.